Ketosis and diabetic ketoacidosis in response to SGLT2 inhibitors: Basic mechanisms and therapeutic perspectives. Issue 5 (23rd February 2017) - Qiu, Hongyu; Novikov, Aleksandra; Vallon, Volker
Summary: Inhibitors of the sodium‐glucose cotransporter SGLT2 are a new class of antihyperglycemic drugs that have been approved for the treatment of type 2 diabetes mellitus (T2DM). These drugs inhibit glucose reabsorption in the proximal tubules of the kidney thereby enhancing glucosuria and lowering blood glucose levels. Additional consequences and benefits include a reduction in body weight, uric acid levels, and blood pressure. Moreover, SGLT2 inhibition can have protective effects on the kidney and cardiovascular system in patients with T2DM and high cardiovascular risk. However, a potential side effect that has been reported with SGLT2 inhibitors in patients with T2DM and particularly during off‐label use in patients with type 1 diabetes is diabetic ketoacidosis. The US Food and Drug Administration recently warned that SGLT2 inhibitors may result in euglycemic ketoacidosis. Here, we review the basic metabolism of ketone bodies, the triggers of diabetic ketoacidosis, and potential mechanisms by which SGLT2 inhibitors may facilitate the development of ketosis or ketoacidosis. This provides the rationale for measures to lower the risk. We discuss the role of the kidney and potential links to renal gluconeogenesis and uric acid handling. Moreover, we outline potential beneficial effects of modestly elevated ketone body levels on organ function that may have therapeutic relevance for the observed beneficial effects of SGLT2 inhibitors on the kidney and cardiovascular system.